Interferon-α disables dendritic cell precursors: dendritic cells derived from interferon-α-treated monocytes are defective in maturation and T-cell stimulation - Dauer, Marc (Blackwell Science Inc, 2003)
Dendritic cells (DC) can be derived from monocytes in vitro by culture with granulocyte–macrophage colony-stimulating factor (GM-CSF) and interleukin-4 (IL-4). It is unknown whether this regimen reflects DC differentiation from blood precursors under physiological conditions. Induction of DC development from monocytes by interferon-α (IFN-α) may occur in vivo during infection or inflammation and thus may represent a more physiological approach to DC differentiation in vitro. Here, we show that incubation of GM-CSF-cultured monocytes with IFN-α does not induce DC differentiation: cells maintain their original phenotype and cytokine secretion pattern. Even after stimulation with pro-inflammatory or T-cell-derived activation signals, IFN-α-treated monocytes do not develop DC characteristics. Addition of IL-4 during stimulation of IFN-α-treated monocytes results in the rapid development of DC-like cells expressing co-stimulatory molecules, CD83 and chemokine receptor CCR7, indicating that some degree of developmental plasticity is preserved. However, DC pre-activated with IFN-α are less effective in inducing allogeneic or antigen-specific autologous T-cell proliferation, produce less IL-12 and express lower levels of CCR7 compared to DC generated by culture with GM-CSF and IL-4. Incubating GM-CSF-cultured monocytes simultaneously with IFN-α and IL-4 does not affect phenotypic maturation of DC, but reduces IL-12 production upon pro-inflammatory activation. We conclude that: (1) IFN-α fails to induce DC differentiation and thus cannot replace IL-4 in generating DC from monocytes in vitro; and (2) the presence of IFN-α prior to or during differentiation of DC from monocyte precursors alters their response to maturation stimuli and may affect their capacity to stimulate T helper type 1 immune responses in vivo.